Assessing Interactive Response of Humic Acid Amended Media and IBA on the Growth and Propagative Capacity of Fig (Ficus carica L.) Stem Cuttings: Interactive Response of Humic Acid Amended Media and IBA - Nadeem, Muhammad; Waseem, Kashif; Khan, Muhammad Sohail; Fatima, Saba; Khan, Ilham; Muhammad, Dost; Arslanoglu, Sahane Funda; Khan, Sabaz Ali (Biological Sciences - PJSIR, 2022)
This study assessed the interactive effects of humic acid (HA) amended growing media (GM) and indole butyric acid (IBA) on a range of parameters determining growth and propagative capacity of Fig (Ficus carica L., var Black Mission) stem cuttings. Cuttings were treated varying IBA concentration (0, 500, 1000 and 1500 mg/L) and propagated in nine GM consisted of sandy loam and clay soils amended with four levels of HA (0, 2.5, 5.0, 7.5 g/m2) and a mixture of sandy loam and clay soils (1:1 v/v) without HA. Ranking of GM changed across IBA concentrations for the majority of parameters, including plant survivability (PS) indicated significant GMxIBA interaction. PS increased with rising IBA concentration (500-1000 mg/L) under lower levels of HA (2.5-5.0 g/m2) across GM. However, the relative response was better in sandy loam based GM. Based on stepwise multiple linear regression, seven parameters viz., percent bud sprout (PBS), shoot length (SL), shoot diameter (SD), leaf area (LA), leaf chlorophyll content (LCC), root to shoot ratio (R/S) and plant N uptake (NUP) explained most of the variance (R2= 99.8%) in plant survival (PS) and acted as the critical determinants of survivability in Fig propagation via stem cuttings. Strong inter relationships existed among the critical traits, thus creating complex trade-offs affecting the overall propagative capacity of Fig stem cuttings. Our approach could be useful in developing indirect selection criterion determining success rates in propagation via stem cuttings.